Feminisme Dalam Wacana Studi Islam - M. Karman (STAI Siliwangi Bandung, 2015)
Gender discourse is interesting in the melee of Islamic thought. Islamic literatures have different views about gender. Classical Islamic literature generally arranged in the perspective of culture androcentric — man became the measure of all things (man is the measure of all things) — if measured in modern, many of which can be assessed gender-biased due to the strengthening system of patriarchal culture that developed in the community. The culture of patriarchy (male dominated) has put women in a subordinate position of men. Male superiority that is contained in almost all the patriarchal system often curb the norms of justice and egalitarianism offered by women for the sake of male power. The patriarchal culture system has been presenting the practices of anti-emancipation of women in society. Indeed, women are ideologically still assumed to serve as a